1991
DOI: 10.1080/00909889109365299
|View full text |Cite
|
Sign up to set email alerts
|

A typology of drug resistance strategies

Abstract: This study examined social influences on adolescents' responses to drug offers. Seventy narrative accounts of both successful and unsuccessful attempts to say no were collected. From these data, the authors developed a typology of both drug offers and drug resistance strategies. In addition, typologies were developed for: who made the offer, what substance was offered, where the offer occurred, and why the subject responded as she or he did. As well, the study revealed the influence of the type of drug, alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 35 publications
0
57
0
Order By: Relevance
“…For example, one model prevention program for youth, keepin' it REAL (Marsiglia and Hecht 2005), is based on the four successful drug resistance strategies used commonly by multi-ethnic samples of adolescents: refuse, explain, avoid, and leave (Alberts et al 1991;Alberts et al 1992;Hecht et al 1992). The success and importance of drug resistance skills-based training is well documented in the prevention literature, both in influencing substance use behaviors and key norms and attitudes toward substance use that are important mediators in substance use etiology (Botvin et al 1994;Griffin et al 2004a, b).…”
Section: Drug Resistance Strategies In Prevention Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one model prevention program for youth, keepin' it REAL (Marsiglia and Hecht 2005), is based on the four successful drug resistance strategies used commonly by multi-ethnic samples of adolescents: refuse, explain, avoid, and leave (Alberts et al 1991;Alberts et al 1992;Hecht et al 1992). The success and importance of drug resistance skills-based training is well documented in the prevention literature, both in influencing substance use behaviors and key norms and attitudes toward substance use that are important mediators in substance use etiology (Botvin et al 1994;Griffin et al 2004a, b).…”
Section: Drug Resistance Strategies In Prevention Programmingmentioning
confidence: 99%
“…In a study on tobacco refusal strategies, Reardon (1989) found that five strategies accounted for 80% of the refusals of tobacco: simple rejection, statement of typical behaviors, expression of attitude/belief, rejection of the person, and walking away. Similar research on the strategies used most commonly by adolescents to resist use of alcohol, tobacco and other drugs led to the identification of four principal strategies: reject, explain, avoid, and leave (Alberts et al 1991). The refuse strategy involves straightforward verbal or non-verbal refusals without explanation.…”
mentioning
confidence: 98%
“…Social skills training compared with pharmacotherapy and psychotherapy in the treatment of unipolar depression. which is designed to equip youth in middle school with a repertoire of skills to resist substance use offers (Gosin, Marsiglia, & Hecht, 2003 (Alberts, Miller-Rassulo, & Hecht, 1991;Kulis, Marsiglia, Castillo, Becerra, & Nieri, 2008;Kulis, Marsiglia, Ayers, Calderón-Tena, & Nuño-Gutierrez, 2011;Marsiglia, Kulis, Martinez Rodriguez, Becerra, & Castillo, 2009). The L2W curriculum is designed to reflect the social contexts in which UAI youth are exposed to substances and culturally influenced ways of responding to offers to use them.…”
Section: Resultsmentioning
confidence: 99%
“…The data for this enterprise emerged from a larger research program designed in part to elicit refusal strategies employed by high school students when confronted with offers of alcohol and other kinds of drugs (see Alberts, Hecht, Miller-Rassulo, & Krizek, 1992;Alberts, Miller-Rassulo, & Hecht, 1991;Hecht, Alberts, & MillerRassulo, 1992;Hecht & Driscoll, in press). The methodology consisted of oral interviews with 59 teenagers conducted in a high school setting in a metropolitan area of the Southwestern United States.…”
Section: Methods and Analysismentioning
confidence: 99%